Motivational pathways from perceived teacher support to student engagement in EFL classes - Zhang, Xiaohui; Kim, Hyun-Ju (Frontiers in Psychology, 2025)
This study investigates the psychological mechanisms through which perceived teacher support influences student engagement in English as a Foreign Language (EFL) reading classes at Chinese universities. Drawing on social support theory and expectancy-value theory, the study examines how teacher support predicts students' motivational beliefs (self-efficacy and intrinsic goal orientation), and how these beliefs, in turn, mediate the link between teacher support and behavioral, emotional, and cognitive engagement. A total of 524 undergraduate EFL learners participated in the study. Data were analyzed using structural equation modeling (SEM), which confirmed the hypothesized motivational mediation pathways. The findings indicate that perceived teacher support significantly predicts these two motivational beliefs, which subsequently lead to higher levels of behavioral, emotional, and cognitive engagement. The results provide theoretical implications for understanding engagement through established psychological constructs and practical guidance for fostering motivation in language learning settings. Overall, this study contributes to educational psychology by applying motivational theories to second language learning contexts and providing evidence-based insights on how to foster student engagement through both contextual and psychological mechanisms.